El Quijote en la Cuba de Fidel Castro - Santonja-Gómez-Agero,, Gonzalo; De Isabel-Estrada,, María Antonia (La Colmena; Núm. 73 (2012), 2017)
Artículo crítico sobre la calidad editorial de las primeras ediciónes del Quijote en la Cuba de Fidel Castro.